DEVELOPMENT OF THE ARCHITECTURE OF THE CLOUDY SYSTEM OF FUSION-RESISTANT STORAGE OF DATA BASED ON THE RESIDUAL NUMBER SYSTEM - Nikolay Nikolaevich Kucherov (Современная наука и инновации)
The article is devoted to the development of an architecture for cloud storage of data based on the residual number system. The evaluation of the developed architecture is made from the point of view of the reliability of stored data and its comparative analysis with existing methods of data storage is carried out.